Effect of Niobium Addition on Corrosion Behavior, Mechanical Properties, and Microstructures of U6Zr Alloys in an Aerated Environment - Masrukan, Masrukan; Handoko, Djati; Djuhana, Dede; Sigit, Rohmad; Al Hasa, M. Husna; Adi, Wisnu Ari; Mardiah, Siti (UI Scholars Hub, 2025)
The effect of Nb addition on the corrosion behavior of U–6Zr alloys within an aerated, demineralized water (DW) environment (pH 5.61) and its correlation of this addition with the mechanical and microstructural properties of the alloys were investigated. The U–6Zr–xNb alloys (x = 1, 4, and 7 wt.%) were synthesized by arc-melting U, Zr, and Nb. Additionally, the samples were mounted and polished, after which they were subjected to electrochemical corrosion analysis using a potentiostat. This evaluation was conducted in a DW medium (pH 5.6), representing an aerated atmosphere, at room temperature (27°C) and a potentiodynamic scan rate of 1 mV/cm2. The results demonstrate that Nb addition to the U–6Zr alloy, which yielded a U–6Zr–xNb (x = 1.4 and 7 wt.%) alloy, influenced the corrosion behavior in media, exhibiting a slightly acidic pH (5.61). Nb additions of up to 4 wt.% caused a continuous increase in the open-circuit potential, corrosion-current density, and corrosion rate (CR); however, these values decreased with the continuous increase in Nb concentrations to 7 wt.%. Furthermore, microstructural analysis via scanning electron microscopy and energy-dispersive X-ray spectroscopy revealed that the corrosion products across almost all U–6Zr–xNb test samples (x = 0, 1, 4, and 7 wt.%) were primarily stable uranium dioxide, which formed a protective layer, followed by oxynitride and zirconium(IV) oxide.Overall, the findings indicated that the varying Nb contents (1, 4, and 7 wt.%) dictated the CR, mechanical properties, and microstructure of the alloys. Ultimately, this study demonstrates the synthesis of U–6Zr–xNb alloys (x = 0, 1, 4, and 7 wt.%) with enhanced performance characteristics.